2019
DOI: 10.1175/jamc-d-18-0241.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Ability of Remote Sensing Observations to Identify Significantly Severe and Potentially Tornadic Storms

Abstract: Remote sensing observations, especially those from ground-based radars, have been used extensively to discriminate between severe and nonsevere storms. Recent upgrades to operational remote sensing networks in the United States have provided unprecedented spatial and temporal sampling to study such storms. These networks help forecasters subjectively identify storms capable of producing severe weather at the ground; however, uncertainties remain in how to objectively identify severe thunderstorms using the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 63 publications
2
37
0
Order By: Relevance
“…Despite recent improvements and science applications with the Bedka and Khlopenkov (2016) method (e.g., Apke et al., 2018; Sandmael et al., 2019), the launch of GOES‐16 and ‐17 satellites and application of this method to 1‐min ABI data (Schmit et al., 2017) revealed some inconsistencies in detection performance from image to image, suggesting that further advancements were needed. This paper provides an enhanced technical description and describes recent advancements to IR‐based deep convection and OT detection algorithms since the version described by Bedka and Khlopenkov (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent improvements and science applications with the Bedka and Khlopenkov (2016) method (e.g., Apke et al., 2018; Sandmael et al., 2019), the launch of GOES‐16 and ‐17 satellites and application of this method to 1‐min ABI data (Schmit et al., 2017) revealed some inconsistencies in detection performance from image to image, suggesting that further advancements were needed. This paper provides an enhanced technical description and describes recent advancements to IR‐based deep convection and OT detection algorithms since the version described by Bedka and Khlopenkov (2016).…”
Section: Introductionmentioning
confidence: 99%
“…This method was found to perform much better than the Bedka et al (2010) version used in previous climatology studies. False OT detections in very cold outflow near to actual OT regions is the most common source of error, though Sandmael et al (2019) showed that agreement between OT detections and severe weather conditions can be further improved using a combination of IR and visible wavelength signals.…”
Section: Overshooting Top Detectionmentioning
confidence: 99%
“…A useful proxy to identify the presence of deep convection development inside a large cloud shield is the presence of an overshooting cloud top (OT) that indicates an updraft strong enough to penetrate through the tropopause. A variety of studies conducted in different locations have shown that OTs are associated with severe weather such as strong winds, heavy rainfall, hail or tornadoes [32][33][34][35][36][37].…”
Section: Goes-16 Extreme Convective Systems Selectionmentioning
confidence: 99%